A Decade of Conflict: Flap Coverage Options and Outcomes in Traumatic War-Related Extremity Reconstruction. Issue 3 (March 2015) - Sabino, Jennifer; Polfer, Elizabeth; Tintle, Scott; Jessie, Elliot; Fleming, Mark; Martin, Barry; Shashikant, Mark; Valerio, Ian L.
Abstract : Background: War trauma patients who have sustained extremity trauma often exhibit extensive zones of injury with multiple concomitant injuries that can contribute to limited coverage options. Thus, flap availability and choice can become critical in the reconstruction algorithm of these severely traumatized patients. The authors' purpose was to analyze the outcomes of muscle and fasciocutaneous flaps during their extremity reconstructive experience to determine which option had better flap and limb salvage outcomes. Methods: A retrospective review of servicemembers treated with flap-based limb salvage from 2003 through 2012 at the National Capital Consortium was completed. Patients were divided into cohorts of patients who underwent muscle or fasciocutaneous flaps. Results: Three hundred fifty-nine flap procedures were performed. Of these procedures, 197 were muscle (55 percent) and 152 were fasciocutaneous flaps (42 percent). There was no difference in overall flap complications between groups (30 percent versus 26 percent; p = 0.475). However, there was a significantly higher flap failure rate in the muscle compared with the fasciocutaneous group (13 percent versus 6 percent; p = 0.030). Although there were more overall extremity complications in the muscle group (59 percent versus 47 percent; p = 0.030), there were no significant differences in soft-tissue infection, osteomyelitis, or amputation rates. Conclusions: There are many flap options that provide adequate coverage in extremity salvage. Complication rates did not differ significantly between muscle and fasciocutaneous flaps, with one exception—flap failure rates were significantly higher in our muscle-based flap cohort of patients. Nonetheless, each of these flap types has utility in our patients based on individual wounding patterns, flap availability for reconstruction, and rehabilitation goals. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Coding Perspective for this article is on page 901.